2015
DOI: 10.1186/s12879-015-0756-8
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B vaccine knowledge and vaccination status among health care workers of Bahir Dar City Administration, Northwest Ethiopia: a cross sectional study

Abstract: BackgroundHepatitis B infection is a major public health problem in Ethiopia. Health care workers are at increased risk of acquiring hepatitis B infection due to occupational exposure. There is effective and safe vaccine against hepatitis B infection. But many health care workers in developing countries are not vaccinated. There is no study in Ethiopia that describes hepatitis B vaccine knowledge and vaccination status of health care workers. Therefore, this study was done to assess hepatitis B vaccination sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
90
8
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(130 citation statements)
references
References 15 publications
(12 reference statements)
17
90
8
1
Order By: Relevance
“…Specifically, studies conducted on health professionals revealed 9.7% prevalence of hepatitis B surface antigen (HBsAg) [17]. On top of that, some studies also reported lower coverage of hepatitis B vaccination among health professionals [1821]. Therefore, this study aimed to assess the attitude and vaccination status of health professionals against hepatitis B virus infection and factors associated with complete immunization.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, studies conducted on health professionals revealed 9.7% prevalence of hepatitis B surface antigen (HBsAg) [17]. On top of that, some studies also reported lower coverage of hepatitis B vaccination among health professionals [1821]. Therefore, this study aimed to assess the attitude and vaccination status of health professionals against hepatitis B virus infection and factors associated with complete immunization.…”
Section: Introductionmentioning
confidence: 99%
“…According to a 2009 World Health Organization report, approximately 2 billion people were affected with HBV worldwide, >350 million suffered from chronic lifelong infection, and more than 1 million individuals die because of cirrhosis and liver cancer every year 1–3. There is high prevalence of HBV infection among Blacks 2.…”
Section: Introductionmentioning
confidence: 99%
“…In Ethiopia, Abeje and others found that 62% of health-care workers were knowledgeable about the HBV vaccine, but only 5% reported receiving all three doses of the vaccination. 9 In Nigeria, Okwara and others found that 29% of health-care workers received vaccination for HBV with 94% being aware of the risks of HBV. 10 Similarly, a study from Sudan showed that although over 90% of hospital staff had knowledge about HBV transmission but less than 50% reported having received vaccination against HBV (one or more doses).…”
mentioning
confidence: 99%